A Dimensionless Equation Linking the Maximum and Minimum Values for Mass (or Energy) and Time (or Length) (Global Journal of Science Frontier Research, 2022)
The James Webb telescope can detect photons in the infrared wavelength from cosmic events with a known intensity and emission frequency. The redshift data from such measurements for photons from the early universe can be used to determine the dimensions of a finite spacetime manifold. Such measurements would differ from predictions using the assumption that space and time are infinite. If these measurements confirm that the spacetime manifold is finite, then there exists a dimensionless ratio between the maximum and minimum dimensions for space and time. Furthermore, the Schwarzschild equation can be used to calculate the total mass of the Universe to determine a dimensionless ratio for the maximum and minimum mass values. The resulting equation derivation is a tribute to the work of Albert Einstein, Alexander Friedmann, Karl Schwarzschild, and Max Planck. The derived dimensionless relationship is M u /m P = t m /t P = ℓ m /ℓ P.